HUBUNGAN PENGETAHUAN DAN HYGIENE PENJAMAH MAKANAN DENGAN ANGKA KUMAN PERALATAN MAKAN - Permatasari, Mutia; Magdalena, Magdalena (Politeknik Kementerian Kesehatan Banjarmasin, 2022)
Abstract : Background : Food safety requirements to be consumed should be the most important first requirement that must be met before other requirements are considered. Microbial contamination in food can come from the environment, raw materials, water, tools used and food handlers. Objective: This study aims to determine the relationship between knowledge and hygiene of food handlers with the number of germs on tableware . Methods: This type of research is a literature study, using a review method on 5 articles. Results: The results of the research on the characteristics of the most touchers are 16-50 years old, and the sex is mostly female. Knowledge of food handlers in the research of Kartika et al (2017) was 68.2%, the research of Poli et al (2014) was less as much as 56.1%. r, Fadhila, et all (2015) and Poli, et all (2014) do not meet the requirements with percentages of 58%, 56.5%, and 100%, respectively. And in the research of Gobel, et al (2015) and Agustiningrum (2018), the number of germs on tableware meets the requirements as much as 67.7% and 85.7%, respectively. Conclusion : There is no relationship between knowledge of food handlers and the number of germs on tableware. There is a relationship between the hygiene of food handlers and the number of germs on eating utensils Keywords: Knowledge Hygiene, Germ number